VALUASI EKONOMI DANAU SENTANI DI KABUPATEN JAYAPURA - HALOMOAN, HUTAJULU (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 7 No 2 (2012), 2012)
Implication processes development at Regency Jayapura begets pressure to in the presence and Sentani's Lake continuity, one that did by society, and also government. That problem as adulterating as water, family and industry waste, is electricity to catch fish, discarding color substance substance goes to lake. That activity cause physical damage, biological, ecosystem and biodiversity that exists in it. Sentani's lake lies at Jayapura's Regency broadly 9.360 ha, one that have natural resources that greatly, and so potentially to be developed as asset at a swoop society income source and region original income. There is role even Sentani's Lake namely as, fishery conducting, fishery catches, fresh water source, tourism, and over transportation. To the effect this research is provide information about Sentani's Lake economic value based decision making in harnessed Sentani's Lake and for management capacity step-up environment and extended development. analisys method that is used is market price approaching, travel cost approaching and approaching contingen valuation method. Result observationaling to point out that Sentani's Lake Economic Value as conducting of fishery reaches Rp.7.507.500.000. Sentani's Lake economic value as producer of fish catches Rp.27.256.250.000/year. Sentani's Lake economic value as source of society drinking water as big as Rp.13.305.500.000. Meanwhile as wisata's object nature reaches Rp.790.759.200/year, added by Lake party performing Sentani as big as Rp.1.750.000.000. Sentani's Lake economic value as transportation namely Rp.569.921.500/ year. Lakes totaled economic value Sentani as big as Rp.51.179.921.700/ years.
Keywords: economic valuation, lake sentani, community, revenue 135